Cameroon : Staff Report for the 2012 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
Despite achieving macroeconomic stability, there is not much improvement in Cameroon's social indicators. To achieve higher and more inclusive growth, the report mentioned that problems in sectors such as infrastructure and a reduction in per capita income and mounting costs of fuel subsidies should be attended to. Due diligence should be exercised to control the expenditure chain and to better track the flow of funds. Better cooperation between national and regional bodies should be initiated for financial stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet